Do Not Test The Safety of Diagnostic Ultrasound Attaching The Probe to Pregnant Small Animals - Maeda, Kazuo (Archives of Clinical and Medical Case Reports, 2019)
A research reported abnormal fetal neuronal migration after irradiation of diagnostic ultrasound attaching the probe to the abdomen of pregnant small animal. Another irradiation of low intensity ultrasound resulted infantile brain damage followed by reduced learning ability. Fetal hepatic cellular apoptosis increased after short irradiation of Doppler ultrasound. Fetal ultrasound examination was restricted after the report.